(untitled) (project baikal, 2019)
The biographical details of Ivan Vladislavovich Zholtovsky are incomplete and controversial. Numerous articles about the architect contain significant contradictions. There were three periods in Zholtovsky’s life: childhood, youth and apprenticeship (1867-1900); achieving fame in architecture (1900-1917) and the Soviet period, which was triumphal and tragic at the same time (1917-1959). Zholtovsky managed to reach the pinnacle of architectural fame neither in the second nor in the third period of his life, though he had every reason to do so, being the most persistent ideologist of traditionalism in architecture. His apprentices idolized him, but the authorities felt that he belonged to a different world and a different culture. They did not believe him, and he had a secret contempt for them. The whole world disappeared with the Master’s death.